Strategi Komunikasi di Media Sosial PT. Pos Logistik Indonesia dalam Membangun Brand Awareness - Kurniawan, Caroline; Rusdi, Farid (Prologia, 2024)
One of the most popular applications today is Tik Tok by providing an opportunity for promotional events. This study aims to describe communication in the Tik Tok social media application of PT Pos Logistics Indonesia's account @officialposlog. The strategy carried out is with the communication mix theory, namely there is a marketing communication strategy, the 4C theory of social media, and the theory of the brand awareness pyramid triangle. The research was conducted using qualitative methods, the results of this research were carried out because they recently started utilizing the social media Tik Tok account @officialposlog. So that the audience knows what services are provided through the @officialposlog social media account starting from stori, stend and super cargo. So the audience recognizes what products are provided by PT Pos Logistics Indonesia so that it becomes an attraction because the content consistently provided by the @officialposlog account communication strategies are made in hard selling and soft selling. So followers of the @officialposlog account see the PT Pos Logistics Indonesia brand as cheap and fast delivery. The author concludes that the aim of his research is to build brand awareness. PT Pos Logistik Indonesia creates social media content consistently on the @officialposlog account. So that Tik Tok follower clients have also spread the word to their closest friends and family to use super cargo products from PT Pos Logistik Indonesia. Salah satu aplikasi yang paling digemari saat ini adalah Tik Tok dengan memberikan suatu peluang untuk ajang promosi. Penelitian ini bertujuan untuk mendeskripsikan komunikasi di aplikasi media sosial Tik Tok akun PT Pos Logistik Indonesia yaitu @officialposlog. Strategi yang dilakukan adalah dengan teori bauran komunikasi yaitu ada strategi komunikasi pemasaran, teori 4C media sosial, dan teori segitiga piramida brand awareness. Penelitian yang dilakukan dengan metode kualitatif, hasil penelitian ini dilakukan karena baru – baru ini mulai memanfaatkan media sosial Tik Tok akun @officialposlog. Dengan banyak persaingan jasa kurir diperlukan brand awareness yang kuat di media sosial Tik Tok @officialposlog. Agar khalayak mengetahui layanan apa saja yang diberikan melalui akun media sosial @officialposlog mulai dari stori, stend dan super kargo. Jadi followers dari akun @officialposlog melihat brand PT Pos Logistik Indonesia murah dan pengiriman cepat. Penulis menyimpulkan tujuan penelitian adalah dalam membangun brand awareness PT Pos Logistik Indonesia membuat konten sosial media secara konsisten di akun @officialposlog. Sehingga klien followers Tik Tok pun juga sudah menyebarluaskan ke teman – teman terdekat dan keluarga untuk menggunakan super kargo produk dari PT Pos Logistik Indonesia.